Elaboración de un modelo de gestión municipal para el Gobierno Autónomo Descentralizado del Municipio del cantón Baba, basado en la participación ciudadana, periodo 2012 – 2014 - Murillo Alarcón, Willian Iván (2012)
The research present whose theme is: “To elaborate of a Municipal Management Model for the Decentralize Autonomous Government for the canton Baba, based in the Citizen Participation, Period 2012 – 2014”; the problem consist in the absence of to adequate Municipal Management Model with incidence negative in the development of the Baba canton, because not dispose of the services various, it is observed a level up of Citizen Participation and economical mobility, with level low development indicator of the population, 40% of the habitants do not dispose of the drinkable water, 25% of the habitants do not dispose of the rubbish picking services, 50% of the city do not pavement. As INEC 2010. Is does formulates with general objectives, To elaborate a Municipal Management Model for the Decentralize Autonomous Government for the canton Baba, based in the Citizen Participation, Period 2012 – 2014, for effect of to improvement the lending services to the population and level up the indicators of city development. The hypothesis of the research present is: To elaborate a Municipal Management Model for the Decentralize Autonomous Government for the canton Baba, based in the Citizen Participation, incidence in the lending services quality and improvement will the development indicators of the population. The project present is very important because breath at to generate benefit for the society, with development level up, through the work fountain generation and the improvement of the public’s services, it is improvement will the Management Model into Decentralize Autonomous Government for the canton Baba, it is increase will the population satisfaction level, reaching the level up of the Citizen Participation in the important decisions which decide the Decentralize Autonomous Government for benefit of the locality. The bibliographic research analyzed the theory mark, with doctrine of the authors which indicated the criteria on the variables Municipal Management Model for the Decentralize Autonomous Government and the Citizen Participation. Moreover was used the technical of the opinion poll, interview, direct observation, was applies at the locality citizenship in the Cantón Baba of the Province Los Rios, employees and authorities which works in the public’s institutions. Moreover was interpreted of the results, with the methodology of statistical graphics and square. The proposal will base in the design of a Municipal Management Model based in the Citizen Participation, which considerate will with points very important: design of the organization structure and functions description of the Municipal Management Model; disposition of norms, sources, politics and procedures; personal capacitating planning; diffusion program to the community; an, design of the feedback system; will use the technical: FODA Matrix, organic structure, Manuals, Plane, Methods Diagram, and to terminate with the economical evaluation, will obtain the economical indicate next: cost benefit coefficient equal 1,15, Return Internal Rate equal 21,64%, Neat Actually Value equal $25,556,18 Pay Back equal to years and to month, superiors on Discount Rate equal 16%, Initial investment equal $22,200,00 Utility Time equal years five, respective, indicates which will simulates the Economical Feasible Investment of the project.